EFEKTIVITAS FUNGSI TERMINAL GERBANGSARI KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Mayandri, Febri; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Terminal built since 1991 and until now has never been used and enforced, it is because of the lack of clarity from the government on this Gerbangsari terminal. The purpose of this study was to determined the effectiveness of Terminal Function Gerbangsari Rengat Western District of Indragiri Hulu. And to investigate the factors that influenced the effectiveness of Terminal Function Gerbangsari Rengat Western District of Indragiri Hulu.The concept of the theory used in this study is the concept of effectiveness Duncan (2008). The research is a qualitative research with descriptive assessment. In the data collection researcher used interviewing techniques, observation and documentation. By using Key Informants as a source of information.From the results of research conducted on the general terminal functions can be assessed not effective, it is because of not achieved some of the existing indicators, as indicators of goal achievement, integration and adaptation. From the several factors that influenced the effectiveness of Terminal functions Gerbangsari Rengat Western District of Indragiri Hulu were the factors that most influenced Facilities gerbangsari terminal that is damaged and no longer maintained, it is very influential on the ineffectiveness of gerbangsari terminal functions. The thing to be done is the repair or renovation of terminal facilities have been damaged. The human resource factor is the driving factor ineffectiveness gerbangsari terminal in terms of human recources are inadequate facilities that are not maintained.Keywords: Effectiveness, Terminal Gerbangsari